Hemodynamic changes after spinal anesthesia in children below the age of four years (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Introduction: Spinal anesthesia has become the anesthesia of choice for most of the surgeries of the abdominal-pelvic region.  Cited with benefits such as lesser risks of apnea, minimal cardiopulmonary alteration, and abnormalities associated with neurocognitive development, it incorporates all components of balanced anesthesia, especially in pediatric surgeries. Encouraging results on the safety, efficacy, and feasibility of spinal anesthesia has increased its utility. The objective of our study was to assess the hemodynamic change occurring in children below four years undergoing lower abdominal and pelvic surgeries following spinal anesthesia.Method: This is a cross-sectional study conducted over 2 years and includes children undergoing surgery of the lower abdomen in Kathmandu Model Hospital. The information was data regarding patients' demography, hemodynamic status prior, during, and after the procedure of spinal anesthesia, measuring systolic blood pressure (SBP), diastolic blood pressure (SBP), mean arterial pressure (MAP), heart rate (HR), sensory and motor block characteristics (modified Bromage scale) and complications.Result: The intraoperative and postoperative hemodynamics did not show major differences. The mean peak sensory level was T4 (C7-T10) during the block. Recovery of sensory and motor blocks was complete in all patients. Modified Bromage scale was 1 in 57(98.27%), 2 h post-surgery.  The average duration of the block was 75 min (30-180). 1(1.72%) patient developed apnea during the surgery.Conclusion: Spinal anesthesia in small children showed minimal variation in intraoperative and postoperative hemodynamics and is a safer mode of anesthesia with sparing of respiratory alterations seen with general anesthesia.